MECHANISM OF CRUDE OIL REMOVAL FROM SAND USING ULTRASONIC ENERGY - MAT SHAYUTI, MUHAMMAD SHAFIQ (2021)
Crude oil-contaminated sand from petroleum wells and oil spill sites pose threats to the environment with its dangerous toxic attributes. Ultrasound holds a potential to be the remediation means owing to its green technology and ability to penetrate inner section of sand particles. However, the mechanism of ultrasonic remediation for oily sand still lacks in comprehension, causing high power consumption and non-optimized treatment. Therefore, the objective of this study was set to deduce the ultrasonic cleaning mechanisms for crude oil-contaminated sand by evaluating the sand, mapping the ultrasonic field, and analyzing cleaning test at various ultrasonic settings. Produced sand from an oilfield in Sabah and beach sand from Terengganu were selected in this study to represent the most common sand casualties by crude oil.